Cover Picture: Facile Synthesis of Zn0.5Cd0.5S Ultrathin Nanorods on Reduced Graphene Oxide for Enhanced Photocatalytic Hydrogen Evolution under Visible Light (ChemCatChem 4/2015). Issue 4 (February 2015) - Shen, Shuling; Ma, Anping; Tang, Zhihong; Han, Zhuo; Wang, Mingjie; Wang, Zhao; Zhi, Linjie; Yang, Junhe
<x xml:space="preserve">Abstract</x> The cover picture shows monodisperse 1D ZnxCd1−xS (ZCS) nanorods on a 2D reduced graphene oxide (RGO) nanosheet. In their Full Paper, S. Shen et al. demonstrate that the 1D/2D model of ZCS/RGO provides a strong contact line‐to‐line interface, which not only is conducive for the fast collection and transportation of photogenerated electrons, but also stabilizes the ultrathin nanorod structure of ZCS during the photocatalytic reaction. The article highlighted by this cover can be found on p. 609 ff. of Issue 4, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>